Cross-cultural study about cyborg market acceptance: Japan versus Spain - Kiyoshi Murata; Mario Arias-Oliva; Jorge Pelegrín-Borondo (European Research on Management and Business Economics (ERMBE), 2019)
Cyborg technologies have left science fiction to become an emerging market. Cyborgs are defined as people who integrate technical elements in their bodies to improve their capacities over innate ones. Taking into consideration the human revolution that this technology can provoke, a cultural approach should be considered in any cyborg market strategy. Our research analyses how ethical awareness, innovativeness perceptions and perceived risk influence the decision to become a cyborg, analysing whether cultures as different as those of Japan and Spain show different results. We focus our study on young higher-education students, collecting a sample of 300 surveys in Japan and 286 in Spain. The findings are surprising. Ethics is the most influential variable on the intention to use this technology. The different cultural aspects concerned with body modification in Japan and Spain constitute a key concern when implanting cyborg technology. Nevertheless, we did not find statistically significant differences in the acceptance of cyborg technology between these two countries.
Keywords: 650; Cyborg; Ethics; Innovation; Technological acceptance